Diferentes níveis de associações entre silagem de milho e feno de alfafa em dietas para bovinos confinados - Savegnago, Caroline Guzi (2023)
The objective of this study was to evaluate the association between corn silage (Zea mays L.) with alfalfa hay (Medicago sativa L.) affects intake, ruminal parameters and animal performance. The research was developed at the Ruminant Teaching and Research Unit of the Federal Technological University of Parana, Campus Dois Vizinhos/PR. Eight crossbred crossbred male bovines were used, with average live weight of 220 kg, in a double Latin square design. The treatments were: 1) 60% corn silage + 40% concentrate; 2) 45% corn silage + 15% alfalfa hay + 40% concentrate; 3) 30% corn silage + 30% alfalfa hay + 40% concentrate and 4) 15% corn silage + 45% alfalfa hay + 40% concentrate. The experimental period was approximately 60 days, with the first 15 days for adaptation to diet and management. The animals were fed ad libitum twice a day throughout the experimental period. The animals on treatment with 30% association of alfalfa hay, has higher for dry matter intake between different treatments. The neutral detergent fiber intake (NDFI), acid detergent fiber intake (ADFI), nitrogen intake (NI) and NIDN was higher in cattle fed with 45% association of alfalfa hay. The treatment with 30% alfalfa hay diet showed the highest value for apparent dry matter digestibility. There was no significant difference for ruminal pH values between different treatments. The highest variation of ruminal pH value, referring to the time of day, was observed for the treatment with only corn silage. The average concentrations of ammonia were higher in the morning than concentrations of ammonia collected 4 hours after fed. The animals on treatment only corn silage and concentrate, has higher average daily gain, followed by treatment with 30% association of alfalfa hay, that has the second higher average daily gain. The association between corn silage and alfalfa hay is an alternative to maintain ruminal pH, increase intake and decrease cost with concentrate, however in this present study this association did not show the highest average daily gain.